Measurable Safety of Automated Driving Functions in Commercial Motor Vehicles Technological and Methodical Approaches - Elgharbawy, Mohamed (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2023)
With the further development of automated driving, the functional performance increases resulting in the need for new and comprehensive testing concepts. This doctoral work aims to enable the transition from quantitative mileage to qualitative test coverage by aggregating the results of both knowledge-based and data-driven test platforms. The validity of the test domain can be extended cost-effectively throughout the software development process to achieve meaningful test termination criteria.